Developing Teaching Material of Research Methodology and Learning with 4D Model in Facilitating Learning During the Covid-19 Pandemic to Improve Critical Thinking Skill - HL, Nur Ihsan; Nasruddin, Nasruddin; Sejati, Andri Estining; Sugiarto, Agus (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research and development aimed to produce teaching materials for research and teaching methodology courses using the 4D model. Teaching materials were arranged based on a 4-D procedure: Define, Design, Develop and Disseminate. The validated teaching materials were tested through small groups of 30 students and large groups of 90 students. It collected data using observation, interviews, documentation, and questionnaires. The data were analyzed qualitatively by data reduction, data presentation, and drawing conclusions and verification. The quantitative analysis was done by processing data from expert reviews and responses from lecturers and students using percentages. The development results were teaching materials validated by four expert validators: content-focused material, curriculum-focused material, learning design, and language. The research and development resulted in a defined stage obtained material elaboration from the point of view of the research methodology of language, mathematics, and geography. The design stage was based on the design validator’s suggestion regarding an attractive appearance on the cover, chapter titles, and the format of the content of the Deepublish textbook. In the development stage, the validation results obtained an average of 76.37% with good qualifications, and the average test decision was feasible with revisions in certain parts. The test results of small group students obtained 75.19% or good qualifications. The results of the large group trial got 76.83% or good qualifications. The research concludes that teaching materials have been compiled based on 4D steps. Based on the findings, the implications of this study show that the teaching materials resulting from the development can be used as material for consideration for teachers in delivering related material under the conditions during the Covid-19 pandemic.